2015
DOI: 10.3390/vaccines3020203
|View full text |Cite
|
Sign up to set email alerts
|

Epitope Prediction Assays Combined with Validation Assays Strongly Narrows down Putative Cytotoxic T Lymphocyte Epitopes

Abstract: Tumor vaccine design requires prediction and validation of immunogenic MHC class I epitopes expressed by target cells as well as MHC class II epitopes expressed by antigen-presenting cells essential for the induction of optimal immune responses. Epitope prediction methods are based on different algorithms and are instrumental for a first screening of possible epitopes. However, their results do not reflect a one-to-one correlation with experimental data. We combined several in silico prediction methods to unra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…The target vaccine has been reported to elicit competent immune responses where T cells act as mediators. The progress in vaccine-designing research recently, has been facilitated by the development of refined assays designed to measure the T-cell responses against various vaccine candidates22. In order to explore T-cell epitopes in peptide sequences, aforementioned reports have accelerated research leading to the development of immunoinformatics methods23.…”
mentioning
confidence: 99%
“…The target vaccine has been reported to elicit competent immune responses where T cells act as mediators. The progress in vaccine-designing research recently, has been facilitated by the development of refined assays designed to measure the T-cell responses against various vaccine candidates22. In order to explore T-cell epitopes in peptide sequences, aforementioned reports have accelerated research leading to the development of immunoinformatics methods23.…”
mentioning
confidence: 99%
“…A recent study reported that in silico analysis enhances the precision and identification of functional CTL epitopes. 49 The authors predicted the CTL epitopes of conserved hepatitis C virus (HCV) proteins and measured their binding affinity with MHC class I molecules in vitro. They also determined the immunogenicity of the identified epitopes in vivo to verify the protective HCV CTL epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…Development of any potential epitope vaccine requires proper prediction and validation of highly immunogenic epitopes that are capable of inducing protective immune response and constitutes the basis of vaccines development as shown in Figure 1 [58]. In fact, significant barrier in designing such kind of vaccine is epitope identification [59].…”
Section: Identification Of the Immunodominant Epitopesmentioning
confidence: 99%